BEROBAT AJA KOK REPOT: TELAAH OPINI PUBLIK KONTROVERSI PERNYATAAN MENTERI KESEHATAN PADA UNGGAHAN AKUN INSTAGRAM @LAMBE_TURAH - Amanda, Shinta Riski; Husna, Asmaul; Fahrimal, Yuhdi (Istek Widuri Jakarta, 2022)
Health insurance is the right of every citizen that must be fulfilled by the state without any discrimination. The statement of the Minister of Health of the Republic of Indonesia regarding the wealthy not being encouraged to use the services of the Social Security Provider Agency (BPJS Kesehatan) has sparked controversy. On social media the news of the Minister of Health's statement was uploaded and received various responses, one of which was on the Instagram account @Lambe_Turah. This account, which focuses on celebrity information and viral events, has 11 million followers so any information shared gets a huge amount of response. This research aims to analyze netizen comments regarding the Minister of Health's statement and will then be analyzed using the perspective of public opinion theory. The method used in this research is qualitative content analysis of public comments on the @Lambe_Turah Instagram account. The analysis is focused on the tone of comments which are categorized into three types, namely, contra, pro, and neutral where each type will be counted in frequency. The results of the study found that the type of tone of comments by netizens was dominated by cons with a total of 1995 comments, while for the tone of comments supporting the narrative of the Minister of Health there were only two comments. The researcher concludes that in the digital era the government must be careful in making public statements. Social media is a public space where government policy narratives quickly get feedback from the public and influence policy formation. This research provides advice in the development of public opinion studies in the social media era.